1996
DOI: 10.1055/s-0038-1650247
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Hypercoagulable State in Nonvalvular Atrial Fibrillation and the Effect of Anticoagulant Therapy

Abstract: SummaryThe purpose of the study was to evaluate alterations of the hemostatic system and the effect of anticoagulant therapy in nonvalvular atrial fibrillation. A set of molecular hematologic markers was measured prospectively in 69 patients with atrial fibrillation and 28 age-matched patients in sinus rhythm. Significantly elevated levels of thrombin-antithrombin III complex (8.5 ± 1.6 vs. 2.5 ± 0.3 αg/1; p <0.001), fibrin monomers (27.1 ± 3.2 vs. 13.4 ± 3.7 nM; p <0.001), D-dimers (788 ± 76 vs. 405 ± 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 21 publications
(24 reference statements)
4
49
2
2
Order By: Relevance
“…Marin, et al 15) reported increased PAI-I, but normal tPA levels, in MS with SR and concluded there was defective fibrinolytic activity. Mitusch, et al 16) reported stimulation of fibrinolysis in patients with AF revealed by elevated plasma tPA levels, but they found no difference in PAI-I. In our study, left atrial tPA and plasmin levels were elevated in patients with AF, reflecting increased fibrinolytic activity, but only tPA was elevated in peripheral blood.…”
Section: Discussioncontrasting
confidence: 62%
“…Marin, et al 15) reported increased PAI-I, but normal tPA levels, in MS with SR and concluded there was defective fibrinolytic activity. Mitusch, et al 16) reported stimulation of fibrinolysis in patients with AF revealed by elevated plasma tPA levels, but they found no difference in PAI-I. In our study, left atrial tPA and plasmin levels were elevated in patients with AF, reflecting increased fibrinolytic activity, but only tPA was elevated in peripheral blood.…”
Section: Discussioncontrasting
confidence: 62%
“…Fibrinogen, PAI-1 concentration, and thrombin-antithrombin III complex levels are elevated in patients with AF compared with matched controls. 2,6,25,26 It is interesting to note that these abnormalities do not develop immediately after the onset of AF. Evidence of activation of fibrinocoagulation is first detectable 12 hours after onset of the arrhythmia and increases progressively with the duration of the episode.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations of the marked reduction in hemostatic markers with conventional anticoagulation have been reported in previous studies. 29,30 The introduction of conventional adjusted-dose warfarin (achieving an INR 2.0-3.0) seems to normalize abnormal levels of thrombogenic markers. 21,29 Plasma levels of vWF antigen are somewhat reduced by OAC treatment.…”
Section: Discussionmentioning
confidence: 99%